Isolation and propagation of classical swine fever virus in porcine Wharton's Jelly mesenchymal stem cells. Issue 4 (1st August 2022) - Tomar, Neelam R.; Bhat, Irfan A.; Bharti, Mukesh K.; John, Jeny K.; Sharma, Veena; Chandra, Vikash; Sharma, G. Taru; Saikumar, G.
Abstract: Classical Swine Fever (CSF) is an extremely infectious and deadly disease of pigs and wild boars caused by the CSF virus (CSFV) which is a member of the Pestivirus genus and the family Flaviviridae . This study was designed to detect the permissibility and replication of CSFV in mesenchymal stem cells (MSCs) monolayer derived from Porcine Wharton's jelly. Porcine Wharton's jelly MSCs (pWJ-MSCs) were ex vivo expanded and propagated for more than 81 generations and third passage pWJ-MSCs were characterized as per standard criteria i.e., growth characteristics, trilineage differentiation potential and molecular characterization for pluripotency and stem cell surface markers. Porcine WJ tissue samples found negative for CSFV by RT-PCR test were processed further for the isolation of pWJ-MSCs and CSFV was propagated over the characterized pWJ-MSCs monolayer. No cytopathic effect was observed, which was consistent with non-cytopathic nature of CSFV. The replication of CSFV in pWJ-MSCs was affirmed by RT-PCR and demonstration of viral antigen in the cytoplasm of virus infected cells by immuno-staining technique. In total, three different CSFV isolates were propagated in pWJ-MSCs. Primary pWJ-MSCs permitted CSFV replication to good titer. To the best of our information, this is the first ever report of isolation of CSFV in pWJ-MSCs.